Le città dItalia tutte piene son di tiranni: tirania, bem comum, cidade e governo na península itálica da segunda metade do século XIV e início do século XV - Letícia Dias Schirm (2018)
This tesis deals with tyranny from Bartolus Sassoferrato (1314-1357) and Coluccio Salutati (1331-1406) treatises. Both authors lived in the Italian peninsula in the second half of fourteenth century and beginning of fifteenth century. Therefore, it is a historical study that approaches a recurring theme in the academic literature as well as among coeval gens du savoir. This is important for understanding the political and policy in the geographical and time frame. It is also relevant to apprehend the tyranny concept historicity that is often understood as self-explanatory. This research aims to understand the tyranny in communes of the region, during the period studied. It is also a goal to notice how concepts as bonum commune, city and government were utilized to define who is tyrant and how to identify him. Therefore, the historical sources of this work are Bartolus da Sassoferratos De Tyranno (On Tyrant); and Coluccio Salutatis homonymous treatise. Besides, there are others works written by these authors that were used as complementary sources, to make possible a better understanding of the scholars thought structure. The objectives are achieved through the comparison between the Bartolus da Sassoferrato (1314-1357) and Coluccio Salutati (13311406) homonymss treatises. At the same time, this comparative approach provides also the meaning identification for terms like tyranny, bonum commune, civitas and regimen to clarify sense and application of these historical concepts.